Haymaker - Schuitema, Adam (Northern Illinois University Press, 2015)
In a political culture infused with debates about personal liberties, the role of government, and even the definition of "freedom" itself, Haymaker tells the story of an isolated Michigan town that becomes the flashpoint for some of the principal ideological debates of our day. When a libertarian organization selects the town as its flagship community, hundreds of its members migrate and settle within the town's borders. The resulting clash with local townspeople is violent and impassioned, even as the line that divides the two sides increasingly blurs.The story follows characters on both of these sides: an eccentric millionaire known as The Man in White, who is still viewed as an outsider even after living in Haymaker for thirty years; a policewoman trained in hostage and suicide negotiations who questions raising children in this new environment; a teenage girl devoted to basketball and her desire to leave home, who has a close but complicated relationship with her uncle, a local who fistfights outsiders in an annual challenge; a libertarian PR expert, just hoping to calm the storm; and the town's mayor, who owns a local diner and is raising a baby daughter as her husband becomes tragically unhinged. A town first settled by lumberjacks, prostitutes, and roughnecks, Haymaker's present becomes as volatile as its past.Haymaker is a story about the failure of best intentions and the personal freedom of individuals to do good or to harm. This witty and politically charged novel will certainly appeal to Michiganders and Midwesterners, but will also interest those looking for an entertaining fictional account of a situation that could plausibly play out in one of the many small, remote towns in the country.
Keywords: Michigan -- Fiction.; Outsiders in literature.; Libertarianism -- United States -- Fiction.; Politics and culture -- Fiction.; Noncitizens in literature.; Strangers in literature.; Michigan -- Romans, nouvelles, etc.; Étrangers dans la littérature.; Politique et culture -- Romans, nouvelles, etc.; LITERARY CRITICISM -- General.; Strangers in literature; Noncitizens in literature; Libertarianism; Outsiders in literature; Politics and culture; Michigan; United States; libertarian organizations, Midwestern fiction, remote towns in the country.; Fiction